Interactive Effect of Ethephon and Shading on the Anthocyanin Composition of Vitis vinifera L. cv. Crimson Seedless - Human, M.A.; Bindon, K.A. (South African Journal of Enology and Viticulture, 2016)
The Vitis vinifera cultivar Crimson Seedless primarily accumulates the anthocyanin peonidin-3-glucoside. The research undertook the study of two factors which could influence the accumulation of anthocyanin in grape berry skins: ethephon application and shade. Ethephon treatment at 200ppm applied one week post-véraison significantly increased the concentration of all anthocyanins in berry skins. Peonidin-3-glucoside was found to increase most significantly in response to ethephon application, and was increased 150% compared with an untreated control. The proportion of 3‑monoglucoside anthocyanins increased in response to ethephon application. A shading treatment did not affect total anthocyanin concentration in berry skins, but the anthocyanin cyanidin-3-glucoside was decreased significantly by shade. Its content was 50% of a sun-exposed control. The observed effects were found to occur at two sites at which the experiment was performed in the Hex River and Paarl regions. Colour development in the Vitis vinifera cultivar Crimson Seedless does not appear to be influenced significantly by bunch shading. The use of commercial growth regulators like ethephon exert a strong influence on anthocyanin production in grape skins of this cultivar, and are therefore a more likely solution to overcome poor colour development in its production.